Evaluating the Use of Artificial Intelligence in Egyptian Insurance Companies - سيد محمد جودة محمد اسماعيل (Maǧallaẗ Al-Buḥūṯ Al-Mālīyyaẗ wa Al-Tiğāriyyaẗ)
تهدف الدراسة إلى عرض استخدام الذكاء الاصطناعي (AI) في شركات التأمين المصرية.تلعب صناعة التأمين دورا حاسما في أي اقتصاد ، والتطورات في الذكاء الاصطناعي لديها القدرة على إحداث ثورة في مختلف جوانب عمليات التأمين ، بما في ذلك الاكتتاب ومعالجة المطالبات وخدمة العملاء واكتشاف الاحتيال وإدارة المخاطر.تحلل هذه الدراسة الفوائد والتحديات والمخاطر المحتملة المرتبطة باستخدام الذكاء الاصطناعي في شركات التأمين المصرية. بالإضافة إلى دراسة الحالة الراهنة لاعتماد الذكاء الاصطناعي فى أنشطة التأمين المتعددة، وتقديم توصيات للتكامل الفعال بين تقنيات الذكاء الاصطناعي وصناعة التأمين داخل السوق المصرية. The study aims to investigate the impact of utilizing Artificial Intelligence (AI) in Egyptian insurance companiesThe insurance industry plays a crucial role in any economy, and advancements in AI have the potential to revolutionize various aspects of insurance operations, including underwriting, claims processing, customer service, fraud detection, and risk management. This study analyzes the benefits, challenges, and potential risks associated with AI implementation in Egyptian insurance companies. Additionally, it examines the current state of AI adoption, and provides recommendations for effective integration of AI technologies with insurance industry.